Reflective member and method for producing glass laminate member

By forming a laminated structure of transparent quartz glass members on the upper and lower surfaces of the opaque silica sintered powder layer, the problem of reflecting heat radiation in the semiconductor industry is solved, and the efficient, stable and high reflectivity reflective members are achieved, and the manufacturing process is simplified.

CN114364641BActive Publication Date: 2025-02-28SHIN ETABU QUARTZ PRODS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080061487.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-08-17
Publication Date
2025-02-28
Estimated Expiration
2040-08-17

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently reflect heat radiation in the semiconductor industry without increasing heat capacity, and traditional reflective layer materials have problems of instability in strength, dust generation and metal impurities.

Method used

采用在不透明二氧化硅质烧结粉体层的上下表面形成透明石英玻璃构件的层合构造,通过加热形成厚度为0.1mm以上的二氧化硅质烧结粉体层,并与石英玻璃构件一体化,形成玻璃层合构件。

Benefits of technology

It realizes reflective members that are free of dust generation, have high damage strength, maintain high reflectivity, and prevent damage in high temperature environments. By simplifying the manufacturing process, flame processing and difficult heating steps are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114364641B_ABST
    Figure CN114364641B_ABST
Patent Text Reader

Abstract

The present invention provides a reflective component and a method for manufacturing a glass laminate component suitable for the reflective component. The reflective component does not generate dust when used, has high destructive strength, and can prevent damage even in a high-temperature environment during production and use while maintaining high reflectivity. A reflective component having a laminated structure in which a transparent quartz glass component is formed on the upper and lower surfaces of an opaque sintered silica powder layer, wherein the thickness of the opaque sintered silica powder layer is greater than 0.1 mm, and the distribution of the film thickness is less than ±0.05 mm. When a load is applied to the transparent quartz glass components on the upper and lower surfaces of the laminated structure in a direction parallel to the laminated structure, the destructive load is increased by 1 cm per 1 cm. 2 The laminate structure has a thickness of 5N or more, and a width of a semi-transparent portion of the laminate structure that is opaque between the opaque sintered silica powder layer and the transparent quartz glass member is 0.01 mm or less at the boundary between the two.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a reflective member having high reflectivity and a glass laminate member. Background Art

[0002] When a high temperature environment such as an electric furnace becomes necessary, in order to prevent the internal heat from being dissipated to the outside, the heating environment is generally covered with an insulating material such as an alumina insulating material. This situation is the same even for a heat treatment furnace used in the semiconductor industry. This insulating material helps to keep the heat and heat uniformity by absorbing heat by itself. Therefore, in the temperature control of the heater, etc., the heat preservation of the insulating material becomes inferior to the temperature responsiveness of the product being treated in the electric furnace. In particular, in the heat treatment step of the semiconductor industry, in order to increase the output, a heat insulation method that does not dissipate heat from the inside and absorbs less heat (small heat capacity) is required.

[0003] Conventionally, for these countermeasures, plates or cylindrical rings of opaque quartz glass having a large number of fine bubbles have been used as heat shielding means. However, in order to effectively shield, it is necessary to arrange several disk-shaped opaque quartz glass plates side by side at the furnace entrance, which results in an increase in heat capacity. Therefore, a heat insulating and heat shielding means with a small heat capacity (small volume) is particularly needed that can shield the heat radiation from the inside of the furnace and reflect it efficiently.

[0004] Therefore, there are technologies such as coating a quartz glass plate with gold or using a reflective layer formed by coating a silica slurry as described in Patent Document 1. However, although metal-based reflective materials such as gold have high performance, they are difficult to use in applications such as the semiconductor industry that do not like metal impurities.

[0005] In addition, in order to obtain high reflectivity, methods using silica slurry, etc. require that the silica particles be partially melted together to form a block structure, which is unstable in strength and will dissolve or peel off even after washing with water or a liquid medicine. Also, since it is porous, it is difficult to remove dirt when it adheres, making it difficult to use in semiconductor industry applications that require high purity.

[0006] Various studies have been conducted to solve these problems. For example, in Patent Document 2, an attempt is made to form a transparent silica layer on the sintered surface of the slurry or the surface of the sintered body of the powder. In these methods, in order to form the transparent silica layer, it is necessary to apply heat at least for melting the silica, and at this time, the silica is melted until the sintered powder layer as the reflective layer, which reduces the reflective performance, or causes deformation due to the change in volume when the transparent layer is formed or the difference in expansion and contraction between the transparent layer and the sintered powder layer, resulting in the occurrence of cracks or damage, which is a so-called problem of difficulty in heating control.

[0007] On the other hand, as proposed in Patent Document 3, an attempt has been made to apply a slurry, sandwich the heat reflective coating in a sealed state between two quartz glass plates, and flame-polish or weld the edges of the quartz plates together. However, the fixing by welding is only around the periphery and cannot be strongly adhered, which has the problem of being easily damaged during production or use as a heat reflective component.

[0008] Prior Art Literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5679591

[0011] Patent Document 2: Japanese Patent No. 5748605

[0012] Patent Document 3: Japanese Patent Application Publication No. 2009-302547 Summary of the invention

[0013] Problems to be solved by the invention

[0014] The object of the present invention is to provide a reflective component which generates no dust when used, has high destructive strength, maintains high reflectivity, and can prevent breakage even in a high temperature environment during production and use, and a method for manufacturing a glass laminate component suitable as the reflective component.

[0015] Means for solving problems

[0016] In order to solve the above-mentioned problems, the reflective member of the present invention is a reflective member having a laminated structure in which transparent quartz glass members are formed on the upper and lower surfaces of an opaque sintered silica powder layer, the thickness of the opaque sintered silica powder layer is 0.1 mm or more, the distribution of the film thickness is ±0.05 mm or less, and when a load is applied to the transparent quartz glass members on the upper and lower surfaces of the laminated structure in a direction parallel to the laminated structure, the load at which the damage occurs is 1 cm 2 When the thickness is 5N or more, the width of the semi-transparent portion of the boundary between the opaque sintered silica powder layer and the transparent quartz glass member in the laminated structure, which is an opaque portion between the two, is 0.01 mm or less.

[0017] The reflectance of the reflective member at a wavelength of 1000 nm to 2000 nm is preferably 60% or more. In addition, the reflectance of the reflective member at a specific wavelength is preferably distributed within a plane of the member at ±5%.

[0018] Preferably, the bulk density of the silica sintered powder layer is 1.3 to 1.5 g / cm 3 .

[0019] The reflective member may include a plurality of the sintered silica powder layers, and may be a reflective member formed by alternately laminating the sintered silica powder layers and the quartz glass member.

[0020] The method for manufacturing a glass laminated member of the present invention is a method for manufacturing a glass laminated member in which quartz glass members are formed on the upper surface and the lower surface of a silica sintered powder layer, and the method comprises: a step of preparing a slurry containing silica glass particles and water; a step of evenly coating the surface of a first quartz glass member with the slurry and drying the coating to form a silica powder layer with a flatness of 0.1 mm or less; a step of placing a second quartz glass member having a surface with a flatness of 0.1 mm or less on the silica powder layer on the first quartz glass member to form an intermediate laminate; and a step of heating the intermediate laminate to form a silica sintered powder layer in which particles in the layer are fixed, the layer thickness is 0.1 mm or more, and the layer thickness distribution is ±0.05 mm, and the silica powder layer is integrated with the intermediate laminate to form a glass laminated member.

[0021] It is preferred that the glass laminate member has a reflectivity of 60% or more at a wavelength of 1000 nm to 2000 nm.

[0022] Preferably, in the step of integrating the intermediate laminate, a layer of 2 The weight (pressing force) is 1g or more.

[0023] Preferably, in the step of heating the intermediate laminate, the heating temperature is 800 to 1350°C.

[0024] The second quartz glass member is a quartz glass member on which a dried silica powder layer is formed, and the intermediate layered body can be formed in a form in which the silica powder layer on the first quartz glass member and the silica powder layer on the second quartz glass member are combined.

[0025] In the step of forming the intermediate laminate, a plurality of first quartz glass components formed with dried silica powder layers can be used, and the second quartz glass component is a quartz glass component without a dried silica powder layer. The plurality of first quartz glass components are laminated in a form in which the silica powder layers are not in contact with each other, and the second quartz glass component is arranged on the silica powder layer of the uppermost first quartz glass component to form the intermediate laminate, thereby forming a glass laminate component including a plurality of sintered silica powder layers.

[0026] Effects of the Invention

[0027] According to the present invention, it is possible to provide a reflective component that does not generate dust when used, has high breaking strength, maintains high reflectivity, and can prevent damage even in a high-temperature environment during production and use. In addition, the following significant effect can be achieved: a manufacturing method that does not require flame processing or difficult-to-control heating steps for a glass laminate component suitable for the reflective component and can be easily manufactured is provided. Furthermore, the following additional effect can also be achieved: since a silica sintered powder layer is coated on the end face of the reflective component by a method such as fusing a glass material, the surface of the glass laminate component can be cleaned with a liquid such as hydrofluoric acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic explanatory diagram showing one embodiment of the method for producing a glass laminate member of the present invention.

[0029] Figure 2 This is an electron micrograph showing a sintered silica powder layer in the glass laminate member of Example 1.

[0030] Figure 3 This is a photograph showing the glass laminated member of Example 1.

[0031] Figure 4 It is a top view showing the measurement points of the thickness measurement in Example 1.

[0032] Figure 5 The microscope photographs show images of the glass laminate structure of Example 1 observed from a cross section. (a) shows an image taken by irradiating light from above the sample, and (b) shows an image taken by transmitted illumination by irradiating light from the back of the sample.

[0033] Figure 6 This is a photograph showing the glass laminated member of Example 2.

[0034] Figure 7 This is a photograph of a cross section of the sample of Comparative Example 1 taken by transmitted illumination. DETAILED DESCRIPTION

[0035] Hereinafter, embodiments of the present invention will be described based on the drawings. However, the drawings are merely illustrative and various modifications may be made without departing from the technical concept of the present invention.

[0036] Figure 1 1 is a schematic diagram showing an embodiment of the method for manufacturing a glass laminated component of the present invention. The method of the present invention is a method for manufacturing a glass laminated component 20 in which quartz glass components (10a, 10b) are formed on the upper surface and the lower surface of a silica sintered powder layer 16, comprising the steps of preparing a slurry 12 containing silica glass particles 13 and water W. Figure 1 (a)]; After the slurry 12 is evenly coated on the surface of the first quartz glass member 10a [ Figure 1 (b)], a step of drying the coating to form a silica powder layer 14 having a flatness of 0.1 mm or less; a step of placing a second silica glass member 10b having a surface having a flatness of 0.1 mm or less on the silica powder layer 14 on the first silica glass member 10a to form an intermediate laminate [ Figure 1 (c)]; the step of heating the intermediate laminate to form a glass laminate component 20 so that the silica powder layer 14 becomes a silica sintered powder layer 16 in which the particles 13 in the layer are fixed and the layer thickness is greater than 0.1 mm and the distribution of the layer thickness is ±0.05 mm, and the silica powder layer 14 is integrated with the intermediate laminate.

[0037] As the silica glass particles 13 used in the slurry 12, known silica glass particles can be used, but silica glass particles with an average particle diameter of 0.1 to 5 μm are preferred. In addition, an organic binder that can be gelled in an aqueous solution due to heat factors can be added to the slurry 12. The content of the silica glass particles 13 in the slurry 12 is not particularly limited, but is preferably 50 to 80% by mass. In addition, Figure 1 In the figure, reference numeral 22 is a container containing the slurry 12 .

[0038] As the quartz glass component, a known quartz glass component can be used without particular limitation, but a transparent quartz glass component is preferred. As the transparent quartz glass component, a colorless and transparent quartz glass component is preferred, and a colorless and transparent quartz glass component having a thickness of 2 mm and a transmittance of 80% or more at a wavelength of 400 to 2000 nm is more preferred.

[0039] The shape of the quartz glass member is not particularly limited, but is preferably a member having a uniform thickness such as a plate, a disk, or a hemispherical shape.

[0040] The thickness of the quartz glass member is preferably thicker than the silica powder layer 15 from the viewpoint of strength, and specifically, is preferably 0.5 mm or more. The upper limit of the thickness of the quartz glass member is not particularly limited, but is practically 10 mm or less from the viewpoint of processing and the like.

[0041] The coating method of the slurry 12 is not particularly limited as long as it can be evenly coated on the surface of the quartz glass member 10a, but it is preferably formed by scraping using a scraper or the like. In the present specification, the so-called even coating means coating with a small distribution of coating thickness. Specifically, it is preferred to form a flat coating in such a way that the distribution of the thickness of the silica powder layer 14 after the coating 12 is dried is within 0.1 mm (± 0.05). When the thickness distribution of the silica powder layer 14 is large, due to poor flatness, the portion where the gap is formed is enlarged in the step of placing the second quartz glass member 10b, the adhesion is reduced, and it is difficult to integrate it by heating.

[0042] In the method of the present invention, the coating of the slurry is dried to form a silica powder layer, which makes it easy to operate in the subsequent steps. When the drying is insufficient, when the coating is clamped by the quartz glass component, the thickness of the silica powder layer changes, or bubbles enter the silica powder layer, resulting in a thin part of the silica sintered powder layer. In addition, when the drying is insufficient and a large amount of water remains, when the quartz glass component is heated, the water becomes water vapor and expands at the bonding place, and there is a situation where integration cannot be performed. Therefore, it is preferred to fully dry the water in the slurry.

[0043] The method for drying the coating film is not particularly limited, but can be carried out in a heating furnace for drying, for example. The drying temperature is preferably lower than the temperature at which the silica glass particles of the silica powder layer are fixed. When the drying temperature is above the temperature at which the particles of the silica powder layer are fixed, a part of the particles of the silica powder layer is fixed. When the quartz glass component is heated for bonding, a part of the particles of the silica powder layer is already fixed, so there is a situation where bonding and integration are impossible. Specifically, the drying temperature is preferably about room temperature (5 to 35°C) to 100°C.

[0044] The dried coating is a silica powder layer with a flatness of 0.1 mm or less, and a second quartz glass member 10b having a surface with a flatness of 0.1 mm or less is placed on the silica powder layer to form an intermediate laminate. In the present specification, the flatness can be measured by placing the material to be measured on a flat platform and measuring it with a laser displacement meter. The flatness of the silica powder layer can be obtained from the in-plane distribution of the height of the silica powder layer.

[0045] In the step of heating the intermediate laminate, if the heating temperature is too low, the particles cannot be fixed and are easily peeled off. If the heating temperature is too high, the bulk density of the silica sintered powder layer becomes high, the sintering degree progresses and partially becomes transparent, reducing the reflectivity. Therefore, the heating temperature is preferably 800 to 1350° C., and more preferably 1100 to 1300° C. The heating environment is not particularly limited, but is preferably an air atmosphere.

[0046] In order to make the intermediate laminate more firmly adhered when heated, a weight (pressing) may be used, preferably one with a weight of 1 cm per layer. 2 The weight (pressing force) is 1g or more.

[0047] The bulk density of the obtained sintered silica powder layer is preferably 1.3 to 1.5 g / cm 3 .

[0048] The thickness of the sintered silica powder layer is preferably 0.1 mm or more, more preferably 200 μm to 1000 μm. When the sintered silica powder layer is too thick, the particles of the silica powder layer are fixed due to heating. At the same time, in the step of integrating the silica powder layer with the quartz glass component, the shrinkage of the silica powder layer during sintering becomes larger than that of the quartz glass component, and the integration cannot be achieved, peeling occurs, or cracks (microcracks) are easily generated on the sintered silica powder layer. In addition, the distribution of the film thickness of the sintered silica powder layer is preferably less than ±0.05 mm.

[0049] Also, in Figure 1 2 shows an example of manufacturing a glass laminate member 20 including a single silica sintered powder layer 16 by using a silica glass member without a dried silica powder layer as the second silica glass member 10 b , but a glass laminate member including a plurality of silica sintered powder layers 16 may be formed. As a method for manufacturing a glass laminate member including a plurality of silica sintered powder layers 16, for example, the following method can be cited: in the step of forming an intermediate laminate, a quartz glass member having a dried silica powder layer is used as the second quartz glass member 10b, and the silica powder layer on the first quartz glass member and the silica powder layer on the second quartz glass member are combined to form an intermediate laminate; or a method of using a plurality of first quartz glass members having dried silica powder layers and a quartz glass member without a dried silica powder layer as the second quartz glass member, laminating the plurality of first quartz glass members in a state where the silica powder layers are not in contact with each other, and arranging the second quartz glass member on the silica powder layer of the uppermost first quartz glass member to form an intermediate laminate; in Figure 1(c) A method of forming an intermediate laminate by laminating a quartz glass member on which a dried silica powder layer is formed on the upper part of the second quartz glass member 10b so that the silica powder layer is in contact with the second quartz glass member 10b. When a plurality of sintered silica powder layers 16 are included, each sintered silica powder layer may be the same or different. For example, a plurality of sintered silica powder layers having different particle size distributions of silica glass particles may be included.

[0050] The above method can easily manufacture a glass laminate member 20 that does not cause peeling, cracks, deformation, etc., and includes a silica sintered powder layer 16 and a quartz glass member 10a, 10b, substantially without a translucent portion having a transparency intermediate between the two, and has a good reflectivity up to the boundary of the quartz glass member.

[0051] The reflective member of the present invention can be easily produced by the method for producing a glass laminate member.

[0052] The reflective component of the present invention is a reflective component having a laminated structure in which transparent quartz glass components (10a, 10b) are formed on the upper and lower surfaces of an opaque silica sintered powder layer 16, wherein the thickness of the silica sintered powder layer 16 is greater than 0.1 mm and the distribution of the film thickness is less than ±0.05 mm.

[0053] In the reflective component of the present invention, the opaque sintered silica powder layer is used as a reflective material. The opaque sintered silica powder layer is preferably a white opaque sintered silica powder layer, and more preferably an opaque sintered silica powder layer that is substantially opaque to light, for example, an opaque sintered silica powder layer having a transmittance of less than 1% for light with a wavelength of 400 to 2000 nm.

[0054] Thermal radiation is usually assumed to be in the infrared range, but in order to suppress energy leakage from the heat treatment space, it is advantageous to have high reflective energy in a wide range from the visible region to the infrared region as much as possible. Preferably, the reflectivity of the reflective member of the present invention is 60% or more at a wavelength of 1000nm to 2000nm. In addition, it is preferred that the reflectivity relative to a specific wavelength is distributed within the surface of the member to be less than ±5%.

[0055] The silica sintered powder layer may have voids between particles as long as it has a clear particle structure. Since reflection occurs at the interface between voids and particles, it is preferred to have moderate voids. However, if the voids are too large, the molten portion between particles will decrease, and the strength of the layer cannot be ensured, or peeling may occur. In addition, when there are fewer voids and more molten portions, the reflective interface decreases, reducing the reflection efficiency of thermal radiation. Therefore, the volume ratio of particles to voids is preferably in the range of 5:5 to 8:2. In addition, the bulk density of the silica sintered powder layer is preferably 1.3 to 1.5 g / cm 3 .

[0056] Since the wavelength to be reflected depends on the particle size of the particles, etc., the particle size is also an important factor. It is preferred that 50% of the particles be distributed within the range of 0.1 to 5 μm.

[0057] Note that the reflective material effect can be obtained even if the material is not silica, but for use at high temperatures, silica, which has a low thermal expansion coefficient and high heat resistance, is most suitable.

[0058] In addition, the thickness of the silica sintered powder layer is preferably 100 μm or more, more preferably 200 μm to 1000 μm. When the silica sintered powder layer is thin, the reflection efficiency of thermal radiation is reduced. For the heat shielding and heat insulation properties of thermal radiation, high reflectivity is preferred. It is effective to have a reflectivity of the same degree or more than that of a metal-based reflective material such as gold, a reflective layer using a known silica slurry, or an opaque quartz glass containing bubbles. The reflectivity can be no less than 60%, and more preferably 80% or more.

[0059] Also, in Figure 1 In the figure, an example of applying a slurry and heating a dried silica powder layer to form a silica sintered powder layer is shown, but in the reflective component of the present invention, the method for forming the silica sintered powder layer is not particularly limited, and the silica powder layer can be formed by a known method, such as directly placing powder, stamping and molding into a layer to form a silica powder layer, and forming the silica sintered powder layer by heating.

[0060] The transparent quartz glass member as the reflective member is preferably a transparent quartz glass member having a thermal expansion coefficient as small as that of the silica sintered powder layer. In the case of opaque quartz glass containing a large number of bubbles, heat radiation may not reach the silica sintered powder layer as the reflective layer and may be scattered by the opaque quartz glass.

[0061] The thickness of the silica glass member is preferably thicker than the silica sintered powder layer because a gap is required in the silica sintered powder layer and strength needs to be maintained by the sandwiched silica glass member.

[0062] The reflective member of the present invention has a semi-transparent portion (with a width of 0.01 mm or less) between the opaque silica sintered powder layer and the transparent quartz glass member in the laminated structure, which has substantially no opacity intermediate between the two, and an opaque silica sintered powder layer having excellent reflectivity up to the boundary with the transparent quartz glass member.

[0063] The interface between the sintered powder layer and the quartz glass member is such that when the molten portion is large, the interface on the particle side is reduced and the reflection efficiency is reduced. On the contrary, when the molten portion is small, there is a risk of peeling off from the interface during use. It is preferred that at least 1% of the area of ​​the molten bonding interface is less than 50%.

[0064] The reflective member of the present invention has excellent strength. When a load is applied to the quartz glass members on the upper and lower surfaces of the laminated structure in a direction parallel to the laminated structure, the load that causes the failure is 1 cm 2 It is 5N or more, preferably 20N or more.

[0065] The reflective component of the present invention includes one or more opaque silica sintered powder layers, and may include multiple silica sintered powder layers, wherein the silica sintered powder layers and the quartz glass component are alternately laminated. When multiple silica sintered powder layers are included, each silica sintered powder layer may be the same or different. Since the reflection wavelength depends on the particle size in the silica sintered powder layer, by configuring multiple layers with different particle size distributions, efficient and wide-range reflection can be achieved.

[0066] The reflective member of the present invention is suitably used in a heat insulation mechanism for a high-temperature heat treatment furnace in a heat treatment step used in the semiconductor industry, where dust generation and metal impurities are small and temperature responsiveness is required.

[0067] Example

[0068] The present invention is further described in detail below with reference to examples. However, it should be understood that these examples are merely illustrative and should not be construed as limiting.

[0069] (Example 1)

[0070] The mixture was mixed with pure water so that the synthetic silica glass particles having an average particle size of 1.5 μm were 60% by mass to prepare a silica slurry.

[0071] A first transparent quartz glass disc with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on a flat workbench, and a silica slurry was flowed on the disc to flatten the surface, and then applied with a scraper. The scraper used a guide member that was 0.2 mm higher than the upper surface of the quartz glass disc.

[0072] The quartz glass disk coated with the slurry was dried at room temperature (23° C.) for more than 5 hours to form a silica powder layer (average thickness of 0.2 mm). The flatness of the silica powder layer was measured by the following method and was found to be 0.07 mm.

[0073] <Measurement method of flatness>

[0074] A quartz glass disk with a dried silica powder layer was measured on a flat platform using a laser displacement meter. The flatness was determined from the in-plane distribution of the height of the silica powder layer.

[0075] A second transparent quartz glass disc with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on the dried silica powder layer to form an intermediate laminate. The flatness of the placement surface of the quartz glass disc was 0.05 mm. The flatness was measured in the same manner as above.

[0076] Then, the intermediate laminate was heated at 1100°C for 3 hours in an air atmosphere to form a glass laminate structure including a transparent quartz glass disk sandwiching an opaque silica sintered powder layer. An electron micrograph of the silica sintered powder layer in the obtained glass laminate structure is shown in Figure 2 In addition, a full photograph of the obtained glass laminated structure is shown in Figure 3 .

[0077] The following measurements were performed on the obtained glass laminated member.

[0078] <1. Method for measuring the thickness of the sintered silica powder layer and the width of the boundary with the quartz glass member>

[0079] The measurement points for thickness measurement in the glass laminate are shown in FIG. Figure 4 .like Figure 4 As shown, the measurement points are 9 points in total, namely, 1 point at the center of the disk (S1), 4 points every 90° near the periphery (S2), and 4 points every 90° between the center and the periphery (S3). The sample for measurement is cut out with a width of 5 mm, and the cross section is enlarged and observed with a microscope or a microscope to measure the film thickness. Figure 5 (a) is a photograph showing a cross-sectional observation image taken from above the sample by illumination with irradiation light.

[0080] Similarly, a cross-sectional observation was performed from the back of the sample using transmitted illumination with irradiated light, and the width of the semi-transparent portion at the boundary between the silica sintered powder layer and the quartz glass disc, that is, at the boundary where the brightness changes between the opaque portion where the silica sintered powder layer appears dark and the transparent portion where the quartz glass disc appears bright, was measured (the lower limit of the measurable value is 5 μm). Figure 5 (b) shows a cross-sectional photograph taken by through-illumination.

[0081] <2. Measurement method of bulk density>

[0082] The bulk density of the silica sintered powder layer was calculated as weight / volume. The weight was obtained by subtracting the weight of the quartz glass member from the total weight, and the volume was calculated by multiplying the coating area by the thickness (average) of the silica powder layer.

[0083] <3. Reflectivity measurement>

[0084] The obtained glass laminated member was sampled from the same position as the measuring point of the thickness measurement of the silica sintered powder layer, and a sample for reflectivity measurement was cut out. An integrating sphere was installed on a measuring instrument LAMBDA950 (manufactured by Perkin Elmer) to measure the reflectivity. In the reflectivity measurement, a spectral reflectance material (manufactured by Labsphere) was used as a standard reflectance material, and the relative reflectivity was measured.

[0085] <4. Strength test>

[0086] For the obtained glass laminated structure, 2 cm × 2 cm samples were taken from the same position as the measuring point of the thickness of the silica sintered powder layer, and 5 samples were cut out for strength test. The upper and lower quartz glass plates were fixed with jigs, and the jigs were set in a strength tester in such a way that a load was applied to the jigs in a direction parallel to the glass plates. The load was applied and the load at the time of destruction was measured. 2 ) Calculate the value per 1cm 2 of the breaking load.

[0087] <5. Durability test in high temperature environment>

[0088] The obtained glass laminate was heated to 1000° C. in an air atmosphere and maintained for 1 hour, and then cooled to room temperature (23° C.) This heating was repeated 10 times to confirm whether breakage, peeling, or cracking occurred.

[0089] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0090] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer (from the end to the center, circumferential direction) is 0.16 to 0.23 mm, and the average film thickness is 0.2 mm. Figure 5As shown in the cross-sectional observation, the boundary between the opaque sintered silica powder layer and the transparent quartz glass plate is clear, and no semi-transparent part (width < 0.005 mm) such as the intermediate layer is observed. The bulk density of the sintered silica powder layer is 1.3 g / cm 3 .

[0091] The reflectivity of the obtained glass laminated member at a wavelength of 1000nm is 85-90%, the reflectivity at a wavelength of 2000nm is 71-76%, and the reflectivity at a wavelength of 1000-2000nm is not less than 71%. At a wavelength of 1000-2000nm, the reflectivity tends to be the minimum at 2000nm, and in the following examples, the reflectivity is evaluated at 2000nm.

[0092] The strength of glass laminate is 10-30N / cm 2 .

[0093] In a durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0094] (Example 2)

[0095] A glass laminate member was obtained by the same method as in Example 1 except that the silica slurry was changed to a silica slurry prepared by the following method. A full photograph of the obtained glass laminate member is shown in Figure 6 The same measurements as in Example 1 were performed on the obtained glass laminated member.

[0096] 60 mass % of synthetic silica glass particles having an average particle size of 1.5 μm and 1 mass % of methyl cellulose were mixed in pure water to prepare a silica slurry.

[0097] The film thickness of the silica powder layer was 0.2 mm on average, and the flatness of the silica powder layer was 0.07 mm.

[0098] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0099] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.18 to 0.23 mm, and the average film thickness is 0.2 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.3 g / cm 3 .

[0100] The reflectivity of the glass laminated member is 73 to 78% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 73%.

[0101] The strength of glass laminate is 15-40N / cm 2 .

[0102] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0103] (Example 3)

[0104] In the heating step of the intermediate laminate, in addition to heating the intermediate laminate at every 1 cm 2 A glass laminate member was obtained by the same method as in Example 2 except that the weight was weighed to 5 g and heat-treated. The same measurements as in Example 1 were performed on the obtained glass laminate member.

[0105] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0106] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.19 to 0.23 mm, with an average of 0.2 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.5 g / cm 3 .

[0107] The reflectivity of the glass laminated member is 72 to 77% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 72%.

[0108] The strength of glass laminate is 20-40N / cm 2 .

[0109] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0110] (Example 4)

[0111] Two samples having a silica powder layer (average film thickness 0.2 mm, flatness 0.07 mm) formed on a transparent quartz glass disc are prepared by the same method as in Example 2. The surface of a silica glass disc without a silica powder layer is overlapped on the silica powder layer of another silica glass disc. Furthermore, a transparently polished third transparent quartz glass plate (flatness of the mounted surface: 0.05 mm) having an outer diameter of 350 mm and a wall thickness of 3 mm is placed on the exposed silica powder layer side to form an intermediate laminate containing two layers of silica powder layers. The intermediate laminate is heat-treated by the same method as in Example 3 to obtain a glass laminate component having two layers of opaque sintered silica powder layers (average 0.2 mm). The obtained glass laminate component is subjected to the same measurements as in Example 1.

[0112] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0113] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.19 to 0.23 mm for the two layers, and the average thickness of each layer of the two layers is 0.2 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.3 g / cm 3 .

[0114] The reflectivity of the glass laminated member is 80 to 85% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 80%.

[0115] The strength of glass laminate is 20-40N / cm 2 .

[0116] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0117] (Example 5)

[0118] Two samples were prepared in the same manner as in Example 2, each of which had a silica powder layer (average film thickness 0.2 mm, flatness 0.07 mm) formed on a transparent quartz glass disc. The silica powder layers of the two silica glass discs were overlapped to form an intermediate laminate containing two continuous silica powder layers. The intermediate laminate was heat treated in the same manner as in Example 3 to obtain a glass laminate containing two continuous opaque silica sintered powder layers (average 0.2 mm). The obtained glass laminate was subjected to the same measurements as in Example 1.

[0119] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0120] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate component are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate component is white and opaque when visually observed. The thickness of each part of the 2-layer silica sintered powder layer is 0.38 to 0.44 mm, with an average of 0.4 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the 2-layer silica sintered powder layer is 1.4 g / cm 3 .

[0121] The reflectivity of the glass laminated member is 78 to 83% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 78%.

[0122] The strength of glass laminates is 20-45 N / cm 2 .

[0123] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0124] (Example 6)

[0125] In the heating step of the intermediate laminate, in addition to heating the intermediate laminate at every 1 cm 2 A glass laminate member was obtained by the same method as in Example 2 except that the weight was weighed to 5 g and heat-treated at 1350° C. for 3 hours in an air atmosphere. The same measurements as in Example 1 were performed on the obtained glass laminate member.

[0126] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0127] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.16 to 0.21 mm, with an average of 0.2 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.5 g / cm 3 .

[0128] The reflectivity of the glass laminated member was 65 to 70% at a wavelength of 2000 nm, which was slightly lower than that of Example 1 and the like, but the reflectivity at a wavelength of 1000 to 2000 nm was not less than 65%.

[0129] The strength of glass laminate is 40-80N / cm 2 .

[0130] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0131] (Example 7)

[0132] In the heating step of the intermediate laminate, in addition to heating the intermediate laminate at every 1 cm 2 A glass laminate member was obtained by the same method as in Example 2 except that the weight was weighed to 5 g and heat-treated at 800° C. for 3 hours in an air atmosphere. The same measurements as in Example 1 were performed on the obtained glass laminate member.

[0133] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0134] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.19 to 0.23 mm, with an average of 0.2 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.3 g / cm 3 .

[0135] The reflectivity of the glass laminated member is 73 to 78% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 73%.

[0136] The strength of glass laminate is 5-10N / cm2 , the strength is lower than that of Example 1.

[0137] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0138] (Example 8)

[0139] In the step of applying the silica slurry to the quartz glass disk, a glass laminate was obtained by the same method as in Example 3, except that a guide member was used in the scraper so as to be 0.15 mm higher than the upper surface of the quartz glass disk. The average film thickness of the silica powder layer formed on the quartz glass disk was 0.15 mm, and the flatness was 0.07 mm. The obtained glass laminate was measured in the same manner as in Example 1.

[0140] No peeling, cracking, or deformation was observed in the obtained glass laminate.

[0141] The transparent quartz glass plates on the upper and lower surfaces of the glass laminate components are colorless and transparent when visually observed. In addition, the silica sintered powder layer in the glass laminate components is white and opaque when visually observed. The thickness of each part of the silica sintered powder layer is 0.1 to 0.17 mm, with an average of 0.15 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width <0.005 mm) such as an intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.4 g / cm 3 .

[0142] The reflectivity of the glass laminated member is 60 to 65% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 60%.

[0143] The strength of glass laminate is 20-40N / cm 2 .

[0144] In the durability test of the glass laminate in a high temperature environment, no breakage, peeling, or cracking was observed.

[0145] (Comparative Example 1)

[0146] 60 mass % of synthetic silica glass particles having an average particle size of 1.5 μm and 1 mass % of methyl cellulose were mixed in pure water to prepare a silica slurry.

[0147] A transparent quartz glass disc with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on a flat workbench, and silica slurry was flowed on the disc to flatten the surface, and then applied with a scraper. The scraper was used as a guide member to make it 1.8 mm higher than the upper surface of the quartz glass disc.

[0148] The quartz glass disc coated with the slurry is dried at room temperature (23°C) for more than 5 hours to form a silica powder layer (average thickness of 1.5 mm). The surface of the dried silica powder layer is heated with a burner flame to make the surface transparent, thereby obtaining a multi-layer body. During the burner heating, cracks are partially introduced into the silica powder layer, and bubbles remain on the transparent surface due to the burner flame. The obtained multi-layer body is measured in the same manner as in Example 1. Figure 7 The figure shows the upper portion of the cross-sectional observation of the sample of Comparative Example 1 photographed by transmitted illumination.

[0149] When the thickness of the transparent layer 28 made transparent by the burner flame is 0.1 to 0.5 mm, the deviation is large. Figure 7 As shown, a semi-transparent portion 26 (width of 0.1 mm or more) is generated between the opaque silica powder layer 24 and the transparent layer 28 formed by the burner flame, and the boundary between the silica powder layer 24 and the transparent portion 28 is unclear.

[0150] (Comparative Example 2)

[0151] 60 mass % of synthetic silica glass particles having an average particle size of 1.5 μm and 1 mass % of methyl cellulose were mixed in pure water to prepare a silica slurry.

[0152] A transparent quartz glass disc with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on a flat workbench, and silica slurry was flowed on the disc to flatten the surface, and then applied with a scraper. The scraper was used as a guide member that was 0.3 mm higher than the upper surface of the quartz glass disc.

[0153] A second transparent quartz glass plate (flatness of the surface on which the plate was placed: 0.05 mm) with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on the quartz glass disk coated with the slurry before the silica coating dried to form an intermediate. About 10 bubbles with a maximum size of 3 mm were observed between the plate on which the plate was placed and the slurry.

[0154] Although the intermediate is per 1cm 2 The film was weighed to 5 g and heated at 1100° C. for 5 hours in an air atmosphere. However, the film peeled off due to thermal expansion of the enclosed air bubbles and could not be bonded.

[0155] (Comparative Example 3)

[0156] 60 mass % of synthetic silica glass particles having an average particle size of 1.5 μm and 1 mass % of methyl cellulose were mixed in pure water to prepare a silica slurry.

[0157] A first transparent quartz glass disc with an outer diameter of 350 mm and a wall thickness of 3 mm was placed on a flat workbench, and silica slurry was flowed on the quartz glass disc. After standing for 1 minute, the disc was tilted and the remaining slurry was poured out.

[0158] The quartz glass disc coated with the slurry was dried at room temperature (23°C) for more than 5 hours. Although the coating was uneven due to the flow trajectory of the slurry, a silica powder layer was formed. The wall thickness of each part of the silica powder layer was 0.18 to 0.47 mm, and the average thickness was 0.3 mm. The flatness of the silica powder layer was 0.2 mm.

[0159] A second transparent quartz glass plate with an outer diameter of 350 mm and a wall thickness of 3 mm (flatness of the surface on which it is placed: 0.05 mm) was placed on the dried silica powder layer to form an intermediate laminate. The intermediate laminate was heat treated in the same manner as in Example 3 to obtain a glass laminate member.

[0160] The obtained glass laminated member was easily peeled, and a sample peeled off during sampling for measurement appeared. The measurement was performed using a sample that was not peeled off.

[0161] The thickness of each part of the silica sintered powder layer is 0.23 to 0.36 mm, with an average of 0.3 mm. In cross-sectional observation, the boundary between the opaque silica sintered powder layer and the transparent quartz glass plate is clear, and no translucent part (width < 0.005 mm) such as the intermediate layer is observed. The bulk density of the silica sintered powder layer is 1.3 g / cm 3 .

[0162] The reflectivity of the glass laminated member is 74 to 85% at a wavelength of 2000 nm, and the reflectivity at a wavelength of 1000 to 2000 nm is not less than 74%.

[0163] The strength of glass laminates is 2 to 10 N / cm 2 , low strength.

[0164] Explanation of symbols

[0165] 10a, 10b: Quartz glass components

[0166] 12: Slurry

[0167] 13: Silica glass particles

[0168] 14, 24: Silica powder layer

[0169] 16: Silica sintered powder layer

[0170] 20: Glass laminated components

[0171] 22: Container

[0172] 26: Translucent part

[0173] 28: Transparent layer

[0174] S1, S2, S3: Measurement points

[0175] W: Water

Claims

1. A reflective member having a laminated structure of at least three layers in which transparent quartz glass members are laminated on the upper and lower surfaces of an opaque silica sintered powder layer, wherein: having a boundary between the opaque silica sintered powder layer and the transparent quartz glass member, The thickness of the opaque silica sintered powder layer is greater than 0.1 mm, the distribution of the film thickness is less than ±0.05 mm, and the bulk density is 1.3 to 1.5 g / cm 3 , When a load is applied to the transparent quartz glass members on the upper and lower surfaces of the laminated structure in a direction parallel to the laminated structure, the load at which the failure occurs is 2 5N or more, In the above-mentioned laminated structure, at the boundary between the opaque silica sintered powder layer and the transparent quartz glass member, a width of a semi-transparent portion having an opacity intermediate between the two is 0.01 mm or less.

2. The reflective member according to claim 1, wherein The reflectivity at a wavelength of 1000nm to 2000nm is above 60%.

3. The reflective component according to claim 1 or 2, comprising a plurality of the sintered silica powder layers, wherein the sintered silica powder layers and the transparent quartz glass components are alternately laminated.

4. A method for manufacturing a glass laminated member, comprising: forming a quartz glass member by laminating a silica sintered powder layer on the upper surface and the lower surface thereof; wherein: Include: The step of preparing a slurry comprising silica glass particles and water; A step of evenly coating the slurry on the surface of the first quartz glass member and drying the coating to form a silica powder layer with a flatness of 0.1 mm or less; A step of placing a second quartz glass member having a surface with a flatness of 0.1 mm or less on the silica powder layer on the first quartz glass member to form an intermediate layer composite body; and By heating the intermediate laminate at 800 to 1350° C., the silica powder layer is formed so that the particles in the layer are fixed, the layer thickness is 0.1 mm or more, the layer thickness distribution is ±0.05 mm or less, and the bulk density is 1.3 to 1.5 g / cm 3 The step of forming a glass laminate component by integrating the silicon dioxide sintered powder layer with the intermediate laminate body, A boundary is formed between the silica sintered powder layer and the quartz glass member.

5. The method for producing a glass laminate according to claim 4, wherein: The glass laminate structure has a reflectivity of 60% or more at a wavelength of 1000 nm to 2000 nm.

6. The method for producing a glass laminate according to claim 4, wherein: In the step of integrating the intermediate laminate, a 1 cm 2 The weight is 1g or more.

7. The method for producing a glass laminate according to any one of claims 4 to 6, wherein: The second quartz glass member is a quartz glass member on which a dried silica powder layer is formed. The intermediate layer composite body is formed in a form in which the silica powder layer on the first quartz glass member and the silica powder layer on the second quartz glass member are combined.

8. The method for producing a glass laminate according to any one of claims 4 to 6, wherein: In the step of forming the intermediate laminate, a plurality of first quartz glass members having a dried silica powder layer formed thereon are used, and the second quartz glass member is a quartz glass member having no dried silica powder layer. The plurality of first quartz glass members are laminated in a state where the silica powder layers are not in contact with each other, and the second quartz glass member is arranged on the silica powder layer of the uppermost first quartz glass member to form the intermediate laminated body, A glass laminate structure including a plurality of silica sintered powder layers is formed.

Citation Information

Patent Citations

  • Device for projecting color picture on screen

    JP1981079591A

  • Detector for relative distance

    JP1982048605A

  • Semiconductor processing apparatus having improved thermal characteristic and method of providing the processing apparatus

    JP2009302547A

  • Production of quartz glass block composite

    JP1996119650A

  • Apparatus and method of manufacturing multilayer quartz glass plate

    JP2004067456A